Defining Benchmarks for Transthoracic Esophagectomy: A Multicenter Analysis of Total Minimally Invasive Esophagectomy in Low Risk Patients. Issue 5 (November 2017) - Schmidt, Henner M.; Gisbertz, Susanne S.; Moons, Johnny; Rouvelas, Ioannis; Kauppi, Juha; Brown, Andrew; Asti, Emanuele; Luyer, Misha; Lagarde, Sjoerd M.; Berlth, Felix; Philippron, Annouck; Bruns, Christiane; et al.
Abstract : Objective: To define "best possible" outcomes in total minimally invasive transthoracic esophagectomy (ttMIE). Background: TtMIE, performed by experts in patients with low comorbidity, may serve as a benchmark procedure for esophagectomy. Patients and Methods: From a cohort of 1057 ttMIE, performed over a 5-year period in 13 high-volume centers for esophageal surgery, we selected a study group of 334 patients (31.6%) that fulfilled criteria of low comorbidity (American Society of Anesthesiologists score ⩽2, WHO/ECOG score ⩽1, age ⩽65 years, body mass index 19–29 kg/m 2 ). Endpoints included postoperative morbidity measured by the Clavien-Dindo classification and the comprehensive complication index. Benchmark values were defined as the 75th percentile of the median outcome parameters of the participating centers to represent best achievable results. Results: Benchmark patients were predominantly male (82.9%) with a median age of 58 years (53–62). High intrathoracic (Ivor Lewis) and cervical esophagogastrostomy (McKeown) were performed in 188 (56.3%) and 146 (43.7%) patients, respectively. Median (IQR) ICU and hospital stay was 0 (0–2) and 12 (9–18) days, respectively. 56.0% of patients developed at least 1 complication, and 26.9% experienced major morbidity (≥grade III), mostly related to pulmonary complications (25.7%), anastomotic leakage (15.9%), and cardiac events (13.5%). Benchmark values at 30 days after hospital discharge were ⩽55.7% and ⩽30.8% for overall and major complications, ⩽18.0% for readmission, ⩽3.1% for positive resection margins, and ≥23 for lymph node yield. Benchmarks at 30 and 90 days were ⩽1.0% and ⩽4.6% for mortality, and ⩽40.8 and ⩽42.8 for the comprehensive complication index, respectively. Conclusion: This outcome analysis of patients with low comorbidity undergoing ttMIE may serve as a reference to evaluate surgical performance in major esophageal resection.